Implementasi Penanaman Karakter Religius melalui Kegiatan Projek Penguatan Profil Pelajar Pancasila di SD Islam Pelangi - Nur Apriliani Apriliani; Dedi Romli Triputra; Muamar Muamar (Journal on Education, 2024)
The background of this research is that there are still students who use slang language that is inappropriate to pronounce, parents lack time to instill religious character at home, infrastructure is still not optimal, all student are taught religious knowledge first before learning begins, wrong one complete elementary school package that provides TPQ and MDTU, students often win championships inreligious competitions. The aim of the research is to determine the religious character of students. This research applies a descriptive qualitative approach. The results of the research show that cultivating religious character in students. These factors can influence religious activities, namely TPQ and MDTU, all students are taught to behave and speak well, are taught about religious from reading juz amma to the Al-Qur’an, how to play the sunnah dhuha prayer, are taught daily infaq which will later students will use it for sharing activities with local people who need it.